Synthetic Route for Racemic Synthesis of Trans-(1R,S, 3R,S)-2-methylene-1,3-dithiane-1,3- dioxide and Reactivity with N-carbethoxy-1,2-dihydropyridine as a Dienophile - Gultekin, Zeynep; Bayrak, Hacer; Frey, Wolfgang (Asian Journal of Chemistry, 2010)
Trans-(1R,S, 3R,S)-2-methylene-1,3-dithiane-1,3-dioxide has been prepared in 22% yield in three steps and cycloaddition of (4a) with N-carbethoxy-1,2-dihydropyridine gave a moderate diastereoselective (76 : 24) in 20% yield. All the major compounds (4b) and (7a) were determined by X-ray analysis.